Low-Volume Cardioplegia and Myocardial Protection in Coronary Artery Bypass Graft Surgery - Tschopp, Samuel; Eckstein, Friedrich; Matt, Peter (The Thoracic and Cardiovascular Surgeon, 2019)
We studied myocardial protection during coronary artery bypass graft surgery using low-volume cardioplegia (Cardioplexol) and minimal extracorporeal circulation (MECC) for different types of coronary artery diseases. In total, 426 consecutive patients were included and divided into four groups: those with left main stem stenosis (n = 45), those with three-vessel disease (n = 200), those with both (n = 141), and those with neither (n = 40). The peak postoperative myocardial markers and 30-day mortality were analyzed. Both myocardial markers and 30-day mortality were significantly elevated in patients with isolated main stem stenosis. We conclude that the use of low-volume cardioplegia and MECC is safe. However, patients with underlying isolated left main stem stenosis might be less protected.
Keywords: coronary artery bypass graft surgery; CABG; myocardial protection; cardioplegia; ischemia/reperfusion; outcomes; surgery; complications